Analisis Buku Teks Sejarah Bagi Siswa SMK Kelas XI - Martin Rizaldi; Anin Lailatul Qodariyah (Program Studi Pendidikan Sejarah Universitas Riau, 2021)
This article aims to describe and analyze the history textbook for grade XI high school students. The research method used to compile this article is the literature review method, namely the method by which reference sources are obtained from scientific books and journals. The result of this research is that history textbooks have a very important role in the ongoing history of learning activities. It can be said that textbooks must contain several feasibility of the contents which are included, namely the completeness of the material, the breadth of the material, the depth of the material and the accuracy of the material. In textbooks there are also advantages and disadvantages as in textbooks that must contain core competencies and basic competencies to support the achievement of learning.